Pengaruh Nyeri Menstruasi Terhadap Regulasi Emosi Atlet Pelajar Putri Futsal Kota Tegal - Hasa Maulana Lazuardi; Anirotul Qoriah; Mugiyo Hartono; Dwi Gansar Santi Wijayanti (Indonesian Journal for Physical Education and Sport, 2024)
Futsal is a sport that has a high intensity of movement. There are differences in physical conditions and disorders felt by male athletes and female athletes. Psychological disorders due to menstrual pain such as irritability, offence, fatigue and others will certainly affect managing emotions properly, so that indirectly emotions can be the reason for decreasing or increasing the performance of athletes. This study aims to determine the effect of menstrual pain on the emotional regulation of female student athletes during futsal training. This research method uses correlational quantitative research methods with simple linear regression analysis. With a population of athletes aged 15-18 years, 50 athletes as a sample. Sampling in this study using purposive sampling technique. The results of data analysis on the coefficient of determination test on the variables of menstrual pain and emotional regulation obtained an R Square value of 0.467 = 46.7%. So it can be concluded that in this study menstrual pain affects emotional regulation by 46.7% and the remaining 53.3% is influenced by other variables or factors not examined in this study.